The Norm___ and the Pathological - Gotkin, Kevin (Disability Studies Quarterly, 2016)
In this paper, I read The Normal and the Pathological by French philosopher Georges Canguilhem for what it can offer disability theory. I examine how the field has already taken up the text but further, I argue for The Normal and the Pathological as a keystone of disability theory (currently taken up with curiously reserved energy). I start with a précis on the text before offering a condensed citation analysis of the book. In the latter part of the paper, I suggest how the monograph might inform current conversations and I offer possibilities for it to deepen and complicate core notions about disability, including the social model, norms, normalcy, and the normate. I conclude by suggesting that Canguilhem’s philosophical intervention can be understood as "propulsive atavism" – an excavation of medical epistemology in order to map and reconfigure its legacies – and I propose this as one methodological template for disability scholarship.